Sugarcane/soybean intercropping with reduced nitrogen addition promotes photosynthesized carbon sequestration in the soil - Zhang, Tantan; Tang, Hu; Peng, Peng; Ge, Shiqiang; Liu, Yali; Feng, Yuanjiao; Wang, Jianwu (Frontiers in Plant Science, 2023)
Introduction Sugarcane/soybean intercropping with reduced nitrogen (N) addition has improved soil fertility and sustainable agricultural development in China. However, the effects of intercropping pattern and N fertilizer addition on the allocation of photosynthesized carbon (C) in plant-soil system were far less understood. Methods In this study, we performed an 13CO2 pulse labeling experiment to trace C footprints in plant-soil system under different cropping patterns [sugarcane monoculture (MS), sugarcane/soybean intercropping (SB)] and N addition levels [reduced N addition (N1) and conventional N addition (N2)]. Results and discussion Our results showed that compared to sugarcane monoculture, sugarcane/soybean intercropping with N reduced addition increased sugarcane biomass and root/shoot ratio, which in turn led to 23.48% increase in total root biomass. The higher root biomass facilitated the flow of shoot fixed 13C to the soil in the form of rhizodeposits. More than 40% of the retained 13C in the soil was incorporated into the labile C pool [microbial biomass C (MBC) and dissolved organic C (DOC)] on day 1 after labeling. On day 27 after labeling, sugarcane/soybean intercropping with N reduced addition showed the highest 13C content in the MBC as well as in the soil, 1.89 and 1.14 times higher than the sugarcane monoculture, respectively. Moreover, intercropping pattern increased the content of labile C and labile N (alkaline N, ammonium N and nitrate N) in the soil. The structural equation model indicated that the cropping pattern regulated 13C sequestration in the soil mainly by driving changes in labile C, labile N content and root biomass in the soil. Our findings demonstrate that sugarcane/soybean intercropping with reduced N addition increases photosynthesized C sequestration in the soil, enhances the C sink capacity of agroecosystems.